Cerebellar Dysfunction in Multiple Sclerosis - Wilkins, Alastair (Frontiers in Neurology, 2017)
Multiple sclerosis (MS) commonly affects the cerebellum causing acute and chronic symptoms. Cerebellar signs contribute significantly to clinical disability, and symptoms such as tremor, ataxia, and dysarthria are particularly difficult to treat. Increasing knowledge concerning the pathophysiology of cerebellar disease in MS from human postmortem studies, experimental models, and clinical trials has raised the hope that cerebellar symptoms will be better treated in the future.